2021
DOI: 10.46542/pe.2021.211.604611
|View full text |Cite
|
Sign up to set email alerts
|

Integration of a virtual pharmacy simulation program “MyDispense” in clinical pharmacy education

Abstract: Background: Since the outbreak of coronavirus disease (COVID-19) and with the absence of conventional social interactions, artificial intelligence and simulation become essential part of sustaining productivity around the world. MyDispense, an online pharmacy simulation, allows students to experience real-life situations in a virtual professional setting to behave as a pharmacist and undertake professional tasks. Aim: The study aim was to see how MyDispense influenced pharmacy students' clinical pharmacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Analysis of student self-reporting of knowledge, skills, and confidence showed no difference between the in-person versus virtual experience; however, there was a strong preference for in-person labs. The other article described the use the 'MyDispense' platform, which simulates a virtual community pharmacy setting where students simulate pharmacy workflow and clinical decision-making skills [25]. A pre-and post-survey (42 questions) was given to assess student perceptions of confidence, satisfaction, motivation, expertise, and decision-making skills.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of student self-reporting of knowledge, skills, and confidence showed no difference between the in-person versus virtual experience; however, there was a strong preference for in-person labs. The other article described the use the 'MyDispense' platform, which simulates a virtual community pharmacy setting where students simulate pharmacy workflow and clinical decision-making skills [25]. A pre-and post-survey (42 questions) was given to assess student perceptions of confidence, satisfaction, motivation, expertise, and decision-making skills.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
“…Two studies clearly showed benefit to using 'MyDispense' to help deliver lab-based classes and support its continued usage [25,58]. The 'MyDispense' software allows for practice with prescription processing, self-care recommendations, and patient assessment in an online setting.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%